Determination of Occupational Disease in Worker with Liver Cirrhosis That Exposed by Vinyl Chloride Superimposed with Hepatitis B Infection - Dewi Sumaryani Soemarko; Aditya Agung Prasetyo (The Indonesian Journal of Community and Occupational Medicine, 2021)
Background: Liver cirrhosis is the final pathological result of various chronic liver diseases that characterized by the formation of regenerative nodules and fibrotic tissue. The etiology of liver cirrhosis are hepatitis C, hepatitis B, alcohol, nonalcoholic fatty liver disease, and can also be caused by chemicals in the workplace. The occupational diagnosis of Liver Cirrhosis that exposed by vinyl chloride superimposed with hepatitis B infection with was performed by using The Seven Steps of Occupational Diagnosis, a method that issued by PERDOKI (Indonesian Occupational Medicine Association-IOMA). The aim of this case report is to determine whether liver cirrhosis in this patient is an occupational disease or not.Case Presentation: Fifty years old man came to Emergency Room with complaints of vomiting black blood since 4 hours. Vomiting blood as much as 5 times with a volume of about 200 cc each time. One day before, patient admitted that his defecation is black, watery, and smell bloody. Volume of defecation was unknown. Three months before, patient complainted that the stomach often felt bloated, enlarged, and got full quickly. There was no icteric in eyes and body.This complaints (vomiting black blood and black stools) were often occured since 2017. In 2017, 2018 and 2020, this patient was hospitalized once while in 2019, the patient was hospitalized twice for this complaint. In 2017, when the complaint first appeared, the patient was declared to have hepatitis B and in 2019, the patient underwent an endoscopy and was said to have enlarged blood vessels in the esophagus, and an abdominal ultrasound was performed and was said to be suspected of liver cirrhosis.This patient works as a family owned chemical industry. The chemical produced is called zamitex, a mixture for paints. These chemicals contain formaldehyde, Vinyl Chloride, and CMC (Carboxymethyl Cellulose). This patient had worked in this field for 21 years, and was exposed to these chemicals. In addition, there are also dangers of heat, awkward positions, and psychosocial.Conclusion: Based on The Seven Steps of Occupational Diagnosis, Liver cirrhosis in this patient can be categorized as an occupational disease superimposed with hepatitis B infection. Liver cirrhosis in this patient can be caused by prolonged exposure to Vinyl Chloride. Vinyl Chloride is known to cause damage to the liver, especially to cause carcinoma of the liver. There is a synergistic effect between exposure to Vinyl Chloride and hepatitis B infection, exacerbating the condition of liver damage. However, because the exposure to Vinyl Chloride has been going on for a longer time, compared to hepatitis B infection, the condition of liver cirrhosis in this patient is still categorized as an occupational disease.